An approximation to the theoretical framework of risks - Sotelo Pérez, María; Sotelo Pérez, Ignacio (Observatorio Medioambiental, 2017)
In the present study a detailed analysis is carried out of the importance it has, in the present moments, the importance of the protection of the Environment of the different "risks, dangers, impacts and disasters". And, is that, the environment that surrounds us must be valued, conserved and protected through effective and efficient preservation measures, so that it not only serves to obtain merely economic growth, but also is integrated into the development models themselves, allowing the generation of an environmental and it is integrated into the development models themselves, allowing the generation of a fair, equitable environmental and ecological environment and, above all, quality, for the whole citizenry.